Physical Education Teacher Education (PETE) in Canada - Melnychuk, Nancy; Robinson, Daniel; Lu, Chunlei; Chorney, David; Randall, Lynn (Canadian Journal of Education/Revue canadienne de l'éducation, 2011)
The purpose of this study was to identify physical education (PE) teacher educators and examine physical education teacher education (PETE) programs presently offered at undergraduate degree-granting Canadian universities. The investigation was conceptualized by issues related to the dislodging of PETE from a central to a marginal role in higher education, contrasting discourses, and the education of children and youth in a post-modern society. In an effort to examine the worldview orientation, underpinning discourses, curricula, structure, and organization of Canada's programs, 36 PE teacher educators from 20 universities completed an online survey. Results enabled a profile of Canada's PE teacher educators and the PETE programs in which they work. Collectively, the findings suggest a need for critical consideration and/or revisiting of programs in light of changing societal and student needs for global, socially, and culturally responsive PETE. Key words: physical education teacher education (PETE), teacher education